KLASIFIKASI KARAKTERISTIK KECELAKAAN LALU LINTAS DI KOTA DENPASAR DENGAN PENDEKATAN CLASSIFICATION AND REGRESSION TREES (CART) - JIWADIANA, I GEDE AGUS; SUKARSA, I KOMANG GDE; SRINADI, I GUSTI AYU MADE (E-Jurnal Matematika, 2015)
The aim of this research is to determine the classification characteristics of traffic accidents in Denpasar city in January - July 2014 by using Classification And Regression Trees (CART). Then, for determine the explanatory variables into the main classifier of CART . The result showed that optimum CART generate three terminal node. First terminal node, there are 12 people were cl a ssified as heavy traffic accident characteritics with single accident, and second terminal nodes, there are 68 people were classified as minor traffic accident characteristics by type of traffic accident front-rear, front-front, front-side, pedestrians, side-side and location of traffic accident in district road and sub-district road. For third terminal node, there are 291 people were classified as medium traffic accident characteristics by type of traffic accident front-rear, front-front, front-side, pedestrians, side-side and location of traffic accident in municipality road and explanatory variables into the main splitter to make of CART is type of traffic accident with maximum homogeneity measure of 0.03252.
Keywords: Classification And Regression Trees; CART; traffic accident; terminal node